REQUIREMENTS FOR FINANCIAL STATEMENTS IN MODERN CONDITIONS (Ideal Journal of Multidisciplinary Research, 2026)
The article examines the importance of the complete and transparent preparation and presentation of financial reporting information, which is an important factor in conducting business and further expanding cooperation with foreign countries and investors. Special attention is paid to the recent work in the field of accounting and auditing in our country, including the importance, necessity and procedure for the transition of business entities to financial reporting standards.
Keywords: Accounting, auditing, international financial reporting standards, financial reporting, reporting standards, financial accounting, tax accounting, financial information, net profit.